Sufistic Education: Contextualization of Moderate-Humanistic Teachings in The Shadziliyah Order, Jombang - Abitolkha, Amir Maliki (Didaktika Religia, 2022)
This study wanted to analyze Sufistic education by the Shadziliyah order under the wrath of KH. Jamaluddin Ahmad Tambak Beras Jombang in the process of forming a moderate-humanistic attitude of pilgrims. The research method used is field studies with a qualitative approach. Extracting data through interviews and observations of non-participants. The results of the study showed that the concept of Syadziliyah order teachings has been able to lead pilgrims to have moderate, wise, and balanced paradigms. Thus, they focus not only on the power of spirituality but also on social aspects, morality, and humanism. Thus, the teaching model applied by the Shadziliyah order is based on the moderation and integration of science between ukhrawi and dunyawi principles as a foundation of behavior in society. In the process of forming social, moral, and spiritual behavior of the pilgrims of the Shadziliyah order, affirming not to be inclusive, individualist, and extreme in wading into the Sufistic world. Moderate attitude is more emphasized in this order, then plus the role of murysid teachers as educators who are not limited as spiritual guides, as well as moral and social educators of their congregations. It is also strengthened by amaliah practiced by the pilgrims consistently who can cleanse their inner aspects so that it has an impact on their behavior, attitude, and actions.